PENGARUH KEAHLIAN AUDITOR, RISIKO AUDIT, SITUASI AUDIT, DAN TEKANAN KETAATAN TERHADAP KETEPATAN PEMBERIAN OPINI DALAM AUDIT LAPORAN KEUANGAN (Studi Empiris Pada Kantor Akuntan Publik di Kota Batam, Padang dan Pekanbaru) - Wadya, Rinalda Prasilia; M, Rasul; Volta, Diyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to determine (1) the effect of the auditor's expertise on the accuracy of giving opinions in the financial statement audit (2) the effect of audit risk on the accuracy of giving opinions in the financial statement audit (3) the effect of the audit situation on the accuracy of giving opinions in the financial statement audit (4) the effect of compliance pressure on the accuracy of giving opinions in the financial statement audit. The data used in this study are primary data with a questionnaire as an instrument. The method used for sample selection was purposive sampling. The population in this study were Public Accounting Firms (KAP) located in Batam, Padang and Pekanbaru City. The number of samples in this study were auditors who worked in 24 KAPs distributed by 72 respondents and returned questionnaires as many as 72 questionnaires (100%). The data analysis technique used in this study is multiple linear regression analysis with the help of SPSS 25.0 for windows. The results of this study indicate that auditor expertise, audit risk, audit situation and compliance pressure are proven to affect the accuracy of giving opinions in auditing financial statements.Keywords: audit opinion, auditor expertise, audit risk, audit situation, compliance pressure.